Mapping the Way through the Court and Enforcement Procedures in Serbia - World Bank (Washington, DC, 2015)
This report complements the Serbia Judicial Functional Review, which assesses the current functioning of the broader judicial system in Serbia and outlines options and recommendations to inform Serbia s ongoing and planned justice reform initiatives in the view of EU accession.1 The aim of this report, however, is to illustrate the steps court users take in order to protect their interests through procedures carried out by courts or bailiffs. The focus is on the difference between the procedure on the books and actual practice. The report analyses these differences in specific types of cases, which had been identified by stakeholders as potentially challenging for those seeking justice:: (1) cases of domestic violence processed by criminal courts, both under the Criminal Procedure Code that was in force from 2001 to 30 September 2013 and under the Criminal Procedure Code which entered into force on 1 October 2013; (2) divorce proceedings, primarily those initiated by alleged victims of domestic violence, together with separate procedures that apply to requests for protective interim measures; (3) cases where one party requests eviction, including both civil proceedings carried out in accordance with the Civil Procedure Code and enforcement proceedings that might follow such proceedings; (4) special enforcement proceedings for settlement of claims in the area of utilities and similar services, which are, after the adoption of the 2011 Act on Enforcement and Security, carried out exclusively by private bailiffs, introduced by this Act. Although the research focused on the functioning of the judicial system in those types of cases, some of its findings inevitably apply to criminal and civil proceedings in general, as well as to certain enforcement proceedings.